Toward a more ethical picture : a study of tragedy news photo use in Singapore newspapers. - Zhou, Qian. (2008)
The purpose of this study is to find the ethical guidelines followed by the Singapore newspaper editors in tragedy news photo use. It is hoped that the findings of this study can help the local newspapers to present the public a more ethical picture of tragedy news in the future.